Northwest history. Mining. Report. 1931-08-12 (1931)
Louise company samples taken M. L. Savage of Kellogg made a recent visit to the property of the Louise Mining company, his latest venture, and returned with samples of low grade ore taken from across the three feet in the face of the drift. The samples show much carbonate with which is mixed more or less quartz and galena.